DNA microarrays in medical diagnostics - Handschuh, Luiza; Magacz, Tomasz; Figlerowicz, Marek (Committee on Biotechnology PAS, 2009)
Many techniques of molecular biology have already been successfully applied in medicine. It seems that in the nearest future, DNA microarrays can also become a useful tool in medical practice. They enable early and precise diagnostics, help to identify disease, predict its outcome and monitor its treatment. DNA microarrays are most frequently applied in medical sciences to detect chromosomal aberrations (CGH arrays), screen single nucleotide mutations (SNP arrays), identify pathogens and profile gene expression. Recently, especially designed DNA microarrays have been introduced to profile the expression of microRNA genes. The majority of projects involving DNA microarrays have been devoted to cancer research. Here, the most prominent examples are described.
Keywords: biotechnology